2015
DOI: 10.1073/pnas.1508040112
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for inhibition of the histone chaperone activity of SET/TAF-Iβ by cytochromec

Abstract: Chromatin is pivotal for regulation of the DNA damage process insofar as it influences access to DNA and serves as a DNA repair docking site. Recent works identify histone chaperones as key regulators of damaged chromatin’s transcriptional activity. However, understanding how chaperones are modulated during DNA damage response is still challenging. This study reveals that the histone chaperone SET/TAF-Iβ interacts with cytochrome c following DNA damage. Specifically, cytochrome c is shown to be translocated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
119
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 55 publications
(128 citation statements)
references
References 42 publications
8
119
0
Order By: Relevance
“…This latter finding is in agreement with previous works in which lysine residues were found to be involved in the binding of C c to cytochrome b c 1 (44,68,71,72), cytochrome c oxidase (67) and GALDH (49), as well as to partners in apoptosis like Apaf-1 (73) and SET/TAF-Iβ (40). …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This latter finding is in agreement with previous works in which lysine residues were found to be involved in the binding of C c to cytochrome b c 1 (44,68,71,72), cytochrome c oxidase (67) and GALDH (49), as well as to partners in apoptosis like Apaf-1 (73) and SET/TAF-Iβ (40). …”
Section: Resultssupporting
confidence: 93%
“…Taking into account the close relation between A. thaliana NRP1 and human SET/TAF-Iβ (Figure 2A), the similar histone-binding properties of the two, and the fact that human C c was recently described as affecting the ability of SET/TAF-Iβ to bind to histones (40), experiments were carried out to determine if C c affects NRP1 in a similar way.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Cc aids in controlling ROS levels by oxidizing superoxide anions (11) and exhibiting peroxidase activity (12); the latter, however, also yields lipid peroxidation (13,14). Furthermore, Cc plays a crucial role in programmed cell death, a process that is only partially understood (15)(16)(17)(18)(19)(20)(21). In this context, a fraction of Cc binds and oxidizes cardiolipin (CL) at the internal mitochondrial membrane, thereby facilitating the release of unbound Cc to the cytoplasm (16,17).…”
mentioning
confidence: 99%
“…In mammalian cells, extramitochondrial Cc interacts with apoptosis activating factor 1 (Apaf-1) in the cytoplasm to spark the caspase proteolytic cascade (15). It has recently been shown that Cc can interact with several other proteins outside the mitochondria in humans and plants (18)(19)(20)(21). The similarities between the Cc signaling networks in both organisms suggest that key programmed cell-death pathways are conserved throughout evolution (22).…”
mentioning
confidence: 99%